Application of multifunctional compositions based on Rheum rhaponticum L. extracts for the elaboration of plant protection products - A. A. Gladcaia (Овощи России, 2020)
Relevance.Extract-based compositions, combining various types of biological activity were created and tested, to reveal the potential of genus Rheum (Polygonaceae)plants bioactive substances. The aim of the work was to determine the composition of bioactive substances in R. rhaponticum L. plants extracts and assess the possibility of their use as a means of protecting vegetable plants from powdery mildew.Materials and methods. The methods of cultivation and research of R.rhaponticum plant materials was carried out at the Institute of Genetics, Physiology and Plant Protection, Chisinau, Republic of Moldova (2012-2019). The subject of our study the bioactive substances of rhubarb roots and leaves were used. Results.The localization zones of anthracene derivatives were identified: in the main parenchyma of the secondary cortex and the parenchyma of the core rays of the rhubarb root. The amount of flavonoids and phenols in the root extract is 2 times more than in the leaf extract. To study the fungicidal and stimulating properties of rhubarb root extract in the control of powdery mildew, we conducted studies in a greenhouse on vegetable plants using artificial infection of seedlings. It was found that the chlorophyll transmittance index of leaves treated with rhubarb root extract increases until the concentration of the extract (R) reaches 1.5% (157.3 rel. units)(In the control – 119.2 rel. units). With increasing concentration of the extract to 2%, the chlorophyll index falls 1.2 times lower than the control values. The highest immunostimulating and fungicidal activity, intensifying with the addition of rhubarb leaf extract, was shown by rhubarb root extract. Its biological effectiveness was high at any intervals between treatment and infection (4 and 72 hours), and was directly proportional to concentration. Adding rhubarb leaf extract to the rhubarb root extract enhances the activity of the composition, and the risk of developing pesticide resistance among plant pathogens decreased.